Adecuacy of pediatric antimicrobial prescribing in the Emergency Department at discharge - Félix Jesús García-Moreno; María Escobar-Castellanos; Rafael Marañón; Arístides Rivas-García; Silvia Manrique-Rodríguez; Andrea Mora-Capín; Cecilia M. Fernández-Llamazares (Elsevier, 2022)
Introduction: In January 2019, the Community of Madrid's Health Department published a guide about the use of antimicrobials in outpatient children. Taking this regional Guide as reference, this study was aimed at estimating the adequacy of the antimicrobial stewardship at discharge from a pediatric Emergency Department (ED). Secondarily, the differences in adequacy according to the diagnosis and the prescriber were studied, and the agreement between this Guide and the protocols of the ED was assessed. Material and methods: An observational, descriptive, retrospective study was conducted on patients under 16 years old, with a diagnosis included in the regional Guide who were discharged from a pediatric ED between March of 2018 and February of 2019. Prescription was considered adequate when the indication, the antibiotic and the posology (dosage, dosing interval, length of treatment and route of administration) were correct. Results: 165 out of 648 (25,5%) infectious diseases processes analyzed received antimicrobial treatment. In 23 processes treated with antimicrobial, the adequacy could not be evaluated due to the absence of data necessary to assess any aspect of posology. Therapy was considered appropriate in 550/625 processes (88.0%). When antimicrobial treatment was prescribed, 70/142 (49.3%) were appropriate and no statistically significant differences in adequacy were found between prescribers. Posology was the worst handled point of the prescription (26.3%). Tract urinary infection, conjunctivitis and otitis media were the pathologies with the lowest adecuacy (44.4%; 50.0% and 52.2%) and presented the highest discrepancy between the Guide and the center protocols (κ = 0.308; κ = 0.000; κ = 0.586). Conclusions: The adequacy of the management of infectious processes to the reference Guide in our pediatric ED was high, but it was below 50% when antimicrobial treatment was required. The degree of adequacy to the local protocols of the center was greater than to the regional Guide. This reveals a discrepancy between the 2 documents that should be analyzed and corrected according to the available scientific evidence. Resumen: Introducción: En enero del 2019 la Consejería de Sanidad de la Comunidad de Madrid publicó una guía acerca del uso de antimicrobianos en niños con tratamiento ambulatorio. El objetivo de este trabajo fue estimar la adecuación de la prescripción de antimicrobianos al alta desde el Servicio de Urgencias Pediátricas (SUP) en pacientes con enfermedades infecciosas, tomando como referencia esta guía regional. Secundariamente, se estudió la variación en la adecuación según el diagnóstico realizado y el facultativo prescriptor, y se valoró la concordancia entre dicha guía y los protocolos del centro. Material y métodos: Estudio observacional, descriptivo y retrospectivo en el que se incluyó a pacientes de 0-16 años con diagnóstico al alta del SUP incluido en la guía regional, entre marzo del 2018 y febrero del 2019. La prescripción se consideró adecuada cuando lo era la indicación, y en su caso, el fármaco elegido, la posología (dosis, intervalo y duración) y la vía de administración. Resultados: Se obtuvo una muestra de la que se analizaron 648 procesos infecciosos, siendo tratados con antimicrobianos 165 (25,5%). En 23 procesos no pudo evaluarse la adecuación a la guía por ausencia de algún dato posológico de la prescripción de antimicrobiano. El manejo terapéutico fue adecuado globalmente en 550/625 procesos (88,0%). En los procesos tratados con antimicrobiano, la adecuación fue de 70/142 (49,3%), sin encontrarse diferencias estadísticamente significativas entre facultativo prescriptor. El motivo de inadecuación más frecuente fue el error posológico (26,3%). Infección urinaria, conjuntivitis y otitis media aguda fueron las entidades clínicas con peor adherencia (el 44,4, el 50,0 y el 52,2% respectivamente) y en las que existió una mayor discrepancia entre guía y protocolos (κ = 0,308; κ = 0,000; κ = 0,586). Conclusiones: La adecuación a las guías de referencia del manejo de procesos infecciosos en el SUP de nuestro centro fue elevada, pero fue inferior al 50% cuando se precisó tratamiento antimicrobiano. El grado de adecuación a los protocolos del centro fue mayor que a la guía de la Comunidad de Madrid, revelando una discrepancia entre ambos que debería ser analizada y corregida de acuerdo con la evidencia científica disponible.